Amino acids determining operator binding specificity in the helix-turn-helix motif of Tn10 Tet repressor. - Wissmann, A (1991)
Each of 22 amino acids in the proposed alpha-helix-turn-alpha-helix operator binding motif of the Tn10 encoded Tet repressor was replaced by alanine and one residue was replaced by valine to determine their role in tet operator recognition by a 'loss of contact' analysis with 16 operator variants. One class of amino acids consisting of T27 and R28 in the first alpha-helix and L41, Y42, W43 and H44 in the recognition alpha-helix are quantitatively most important for wild-type operator binding. These residues are probably involved in the structural architecture of the motif. A second class of residues is quantitatively less important for binding, but determines specificity by forming base pair specific contacts to three positions in tet operator. This property is most clearly demonstrated for Q38 and P39 and to a lesser extent for T40 at the N-terminus of the recognition alpha-helix. The contacted operator base pairs indicate that the N-terminus of the recognition alpha-helix is located towards the palindromic center in the repressor-operator complex. Although the orientation of the recognition alpha-helix in the Tet repressor-tet operator complex is inversed as compared with the lambda- and 434 repressor-operator complexes, the reduced operator binding of the TA27 mutation in the first alpha-helix suggests that the hydrogen bonding networks connecting the two alpha-helices may be similar in these proteins.(ABSTRACT TRUNCATED AT 250 WORDS)